Innovating Assessment Through the use of Tailored Testing on Student Achievement of Senior Secondary Mathematics Students in Kogi State - Omale, Onuh (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The research aimed to assess the effectiveness of tailored testing on the academic performance of senior secondary three (SS3) Mathematics students in Kogi State. Methodology: The study employed a quasi-comparative experimental research design, involving a total of 492 students from the state. The sample specifically consisted of SS3 Mathematics students, and a combination of disproportionate and purposive sampling techniques was utilized for participant selection. Data collection involved the use of three instruments, including a 50-item National Examination Mathematics past Questions paper (NECOMPQ). The study was guided by two research questions and two hypotheses. Descriptive statistics, such as mean and standard deviation, were employed to address the research questions, while the t-test statistic was utilized to assess the hypotheses. Findings: The findings indicated a notable difference in the mean achievement scores between high and low-ability students when using standardized test items. In contrast, there was no significant difference in mean achievement scores between high and low-ability students when tailored testing was employed. Conclusion: It can be concluded that when appropriate assessment tools are employed, there is a higher likelihood of revealing a student's true academic ability. Consequently, the study offers the following recommendations: Emphasize the importance of using tailored testing methods in educational assessment practices to better accommodate students with varying abilities. Encourage educators and institutions to consider the individualized needs and capabilities of students when designing assessment instruments. These recommendations are grounded in the research's findings and underscore the potential benefits of tailored testing in enhancing the accuracy of academic assessments.